Developing primary mathematics teaching : reflecting on practice with the knowledge quartet - Rowland, Tim (SAGE, 2009)
This title helps readers to become better, more confident teachers of mathematics by enabling them to focus critically on what they know and what they do in the classroom. Each chapter includes practical activities, lesson descriptions and extracts of classroom transcripts to help teachers reflect on effective practice.